THE IMAGE OF LONDON AND ROYAL POWER IN CONCORDIA POEM (City: History, Culture, Society, 2020)
The article analyzes the royal entry of Richard II into the city of London in August 1392. The main study focused on the analysis of narrative source – the poem «Concordia facta inter regem et cives Londonie», which was written by Carmelite monk Richard Maidstone. The main functions of the poem were identified, and the ideological aspects were disclosed. Besides, the text analysis demonstrates the strong and weak points of propaganda poetry. The article demonstrates the importance and symbolism of the royal entry, as a union of the king with his capital and all its citizens. The content of the ceremonial entrance allows us to consider it in the context of the problematic relations between the city and royal power. It displays main ideas of Richard of Maidstone that showcase his view of the events of August 1392, where some parts are exaggerated or even have embroidered facts, to display all royal benefits in front of London. This piece illustrates the role which the royal entry had in times of the reign of Richard II. It was one of the ways to establish relations and regulate relations between citizens and their ruler. During the process of the ceremonial, the king demonstrated all might and strength of his power, thereby trying to sacralize himself and enhance the authority of the crown. Emerging of monarch's sacred image was traced using the «Concordia». The study focuses on the ideological usage of allegoric symbols by Richard II, which emphasizes the piety and mercy of the king. Thus the king wanted to increase the authority of the crown and applied all possible methods to achieve that, including royal entrances. The features and significance of the ceremonial entry into the life of London were identified, as well as the importance of holding such an event in the formation of the royal image of Richard II Plantagenet. The article explores the ways of using such ceremonial events for the communication of the monarch with his people. It is argued that one of the forms of medieval representation of power is a royal entry.  It is shown that the ceremonial entrances reflect a certain degree the notion of royal power in the late Middle Ages.
Keywords: king Richard II; Richard Maidstone; London; royal entry; image